Synthesis, Characterization and Biological Activities of Schiff's Base Metal Complexes Derived from Hydroxy Trizene and Aromatic Aldehyde - Shekhawat, A. S.; Singh, N. P.; Chundawat, N. S. (Journal of Scientific Research, 2022)
Schiff's bases are one of the important classes of the ligands, which are obtained by the condensation of amine and aromatic aldehyde. The metal complexes of Schiff's bases are widely considered because they show excellent biological activities. Such as antimicrobial, antitumor, antibacterial, and anti-fungal properties. The present studies deal with synthesis and characterization of Schiff's base transition metal complexes synthesized from general formula (ML) M=Co(II) and Cu(II); L = Schiff's base ligand derived from hydroxy trizene and aromatic aldehyde. The Synthesized complexes were characterized by physical and spectral analysis such as FTIR, 1HNMR, and XRD. They were also tested in vitro biological activities. The Schiff base behaves as a bidentate ligand with O and N donors and binds to metal ions via hydroxy group oxygen and azomethane nitrogen. The Schiff's base ligands and Metal complexes' structure was confirmed by modern instrumental techniques viz, FTIR and 1HNMR. The in-vitro antibacterial studies were carried out against S. aureus, E. coli, and P. Aeruginosa and anti-fungal activities C.albicans, A. clavatus. The result shows that the complexes have excellent biological activities.